Expression characteristics of immune factors in the yak (Bos grunniens) testis. Issue 9 (23rd July 2021) - Zhang, Qian; Cui, Yan; Yu, Sijiu; He, Junfeng; Pan, Yangyang; Bai, Zhanchun
Abstract: The goal of this study was to characterize and evaluate the main markers of macrophages, T lymphocytes, B lymphocytes and plasmocytes in the testis of juvenile and adult yaks by quantitative real‐time polymerase chain reaction and immunohistochemistry. Within the same age group, the mRNA expression of CD68 was always highest, followed by that of CD3ε, CD79α, IgG and IgA . Moreover, CD68, CD3, CD79α, IgA and IgG positive cells were all located in the testicular interstitial tissues of juvenile and adult yaks. In the same age group, the frequency of CD68 positive macrophages was higher than that of CD3 positive T lymphocytes, which was followed by that of CD79α positive B lymphocytes and IgA and IgG positive plasmocytes. No significant difference was observed between the B lymphocyte and plasmocyte frequencies in yak testes. Furthermore, CD68, CD3ε, CD79α, IgA and IgG mRNA expression levels and the frequencies of CD68, CD3, CD79α, IgA and IgG positive cells increased from juveniles to adults. Similarly, the frequencies of CD68, CD3, CD79α, IgA and IgG positive cells also increased with age. These results suggest that in the yak testis, the immune defence system against pathogens might primarily comprise macrophages and T lymphocytes in the testicular interstitial tissue. Moreover, the testicular immune environment may mature and expand to a fully functional state in adult yaks. The low frequencies of B lymphocyte and plasmocyte in yaks, differing from those in rodents and humans, might be related to the fact that yaks live in low‐oxygen plateaus.